USING DUET TECHNIQUE OF ENGLISH SONG ON THE TIKTOK APPLICATION TO STUDENTS' SPEAKING SKILLS - Monaris Pasaribu; Sri Inca Gultom; Stephania Denika Br Sagala; Sri Ninta Tarigan; Tiarnita Maria Sarjana Siregar (Jurnal Basataka (JBT), 2022)
This study focuses on the topic of teaching students to talk more fluently in English by using duet approaches. The researchers employed qualitative techniques to meet their goals. The researcher may choose to gather information through questionnaires. There were 20 students in the class X MIA at SMA Swasta GKPI Padang Bulan who made up the study's population. For the research to go without a hitch, three songs have been prepared: Perfect by Ed Sheeran, Talking to The Moon by Bruno Mars, and I'm Yours by Jason Mraz. Pre speaking activities, speaking activities, and post speaking activities were the three sections into which research was separated throughout two meetings. Assessment is broken down into three components: pronunciation, fluency, and comprehension. Students’ present a duet using their own knowledge during the first meeting. The researchers then provided an explanation before to testing the students at the second meeting. The study's finding is that using the duet technique helps students develop their speaking abilities.